PERAN KONTRAK PSIKOLOGIS SEBAGAI PENGUNGKIT KINERJA PELABUHAN PERIKANAN NUSANTARA KARANGANTU BANTEN - Saefudin Saefudin; Bambang Dwi Suseno; Uli Wildan Nuryanto (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The problem of the research that needs to be solved is the performance deficiency of the UPT PPN Karangantu in maintaining the potential loss of the maximum sustainability yield (MSY) in the marine area of Banten Province. The objectives of the study are: (1) to examine the effect of work motivation on psychological contracts at the UPT. Karangantu PPN; (2) to examine the effect of work discipline on psychological contracts; (3) to test the effect of work motivation on performance; (4) to test the effect of work discipline on performance; (5) to test the influence of psychological contracts on performance and (6) to test the effect of work motivation on work discipline in the UPT. Karangantu PPN.The framework of thought in this study included the independent variables namely Motivation (X1), Work Discipline (X2) and intervening variables namely Psychological Contracts (X3), while the dependent variables are Performance (Y). Considering the population was smaller than 100 respondents, it was determined to use saturated sampling techniques, which is the sampling by making all members of the population into samples or often called population research or census (Ferdinand, 2014). Therefore the sample in this study was 70 respondents. Based on descriptive data process, it showed that the PP Karangantu employees are mostly the male as many as 63 people or 90.0% and female respondents as many as 7 people or 10.0%. Based on the processing data of the Karangantu VAT staff, some of the largest respondents were aged between 26-40 years as many as 48 people or 68.6% and respondents aged 41-58 years were 22 people or 31.4%.The results first showed that the work motivation had a positive and significant effect on psychological contracts. Second, the work discipline does not have a positive and significant effect on psychological contracts. Third, psychological contracts are able to act as intervening variables which are positive and significant in the relationship between work motivation and performance. Fourth, psychological contracts are able to act as intervening variables which are positive, but not significant in the relationship between work discipline and employee performance. Fifth, Psychological Contracts have a positive and significant effect on performance and the six work disciplines have a positive and significant effect on the work motivation of employees UPT Karangantu PPN.